Decomposing the impacts of overeducation and overskilling on earnings and job satisfaction: An analysis using REFLEX data - Nuria Sánchez-Sáncheza; Seamus McGuinness (The Economic and Social Research Institute (ESRI), 2011)
This paper uses the REFLEX dataset to test the hypothesis that the generally observed negative impacts of overeducation and overskilling on both job satisfaction and earnings can be attributed to under-utilisation in specific job related skills. We find that the penalties to both forms of mismatch are insensitive to the inclusion of controls for overskilling in a wide range of job specific competencies. The research suggests that the problem of mismatch relates to an inability for fully utilise general or innate ability as opposed to specific areas of acquired learning. The analysis suggests the problem of mismatch can only be effectively addressed by raising general levels of job quality within economies and this, in turn, presents serious challenges for policy.
Keywords: 330; overeducation; overskilling; job satisfaction; earnings